EFEK DOPING Ni (II) PADA AKTIFITAS FOTOKATALITIK DARI TiO2 UNTUK INHIBISI BAKTERI PATOGENIK - Rilda, Yetria; Dharma, Abdi; Arief, Syukri; Shaleh, Baharuddin (Makara Journal of Science, 2010)
Influence of Co-Doping of Ni (II) on Photocatalytic Activity of TiO2 for Pathogenic Bacteria Inhibition. Nanoparticle titanium dioxide (TiO2) has most attention in the past decade, since it can be applied as alternative material on sterilization photocatalyst process. This research focused on increasing performance of titania such as structure, particles size and surface area through Ni ion doped on TiO2 surface by sol-gel technique. Product were used to design of a photobioreactor for sterilization process from pathogenic bacteria such as Escherichia coli, Staphylococcus aureus and Bacillus subtilis. Product were characterized using Thermogravimetric-Differential Thermal Analysis (TG-DTA), X-ray Diffraction (XRD), Transmition Electron Microscopy (TEM), Scanning Electron Microscopes-Energy Dispersive X-Ray Spectroscopy (SEM-EDX) dan Brunauer-Emmet-Teller (BET). Titanium dioxide with anatase structure have 12.1 nm in particles size and surface area 49.6 m2 / g that have higher inhibition rate to bacteria cell. Photobiocatalytic reaction was carried out in various TiO2-Ni concentration and UV irradiation times. The anti bacteria from TiO2-Ni to all bacteria cell suspension after UV irradiated at λm : 365 nm has good synergistic effect. Effect of mechanical treatment by sonicator showed the increasing inhibition rate around 4% for 120 minute irradiation. Inhibition rate optimization for each bacteria gave different efficiency inhibition to TiO2-Ni concentration 1.5-2.0 g/L. TiO2-Ni powder inhibited growth of Escherichia coli, Staphylococcus aureus around ≥ 95% for 120 minute irradiation, while Bacillus subtilis resistance with inhibition percentage rate only 88.1%.